Serum ZAG Levels Were Associated with eGFR Mild Decrease in T2DM Patients with Diabetic Nephropathy - Lingling Xu; Weihong Yu; Meng Niu; Caixia Zheng; Bin Qu; Yan Li; Jing Wang; Ping Huang; O. Wang; Fengying Gong (International Journal of Endocrinology)
Objective. To investigate the changes of serum zinc-α2-glycoprotein (ZAG) in type 2 diabetes mellitus (T2DM) with eGFR mild decrease. Subjects and Methods. A total of 438 T2DM patients (61.3 ± 4.0 y) were recruited and the demographic, anthropometric, and biochemical parameters were all collected. Serum ZAG levels were determined by commercially available ELISA kits. Results. The proportion of T2DM patients with the high tertile ZAG levels was 11.9% higher in patients with mildly decreased estimated glomerular filtration rate (eGFR) (<90 mL/min/1.73 m2) than those with the low tertile ZAG levels P=0.038. The probability of the eGFR<90 mL/min/1.73 m2 in patients with the high ZAG levels was 94% higher than those with the low serum ZAG levels after adjusting for age, gender, and education [OR = 1.94, 95% CI (1.17–3.23), P=0.0094]. This phenomenon was more likely to be observed in the condition of uACR ≥ 2.7 mg/mmol, WC ≥ 90 cm for men, or WC ≥ 85 cm for women. Conclusion. Serum ZAG levels were firstly found to be related with eGFR in T2DM patients. The patients with the high tertile ZAG levels were more likely to have mildly eGFR decrease, especially for female patients with higher uACR and bigger WC.